2020
DOI: 10.1002/capr.12335
|View full text |Cite
|
Sign up to set email alerts
|

Rolling with resistance: A client language analysis of deliberate practice in continuing education for psychotherapists

Abstract: workshops, the dominant model of postgraduate training, are not systematically tested and in fact are limited for improving therapist performance. This is because they typically focus more on knowledge than skill (e.g., Davis et al., 1999;Owen et al., 2016;Taylor & Neimeyer, 2017). Workshops on motivational interviewing are one of the few areas where therapist learning has been studied versus assumed (MI;Miller & Rollnick, 2002). MI workshops tend to involve relatively higher amounts of practice, and reviews o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…As expected, the Traditional workshop trainees lowered their level of Support with simulators versus the community volunteers, but the DP group increased Support. Findings from Di Bartolomeo, Shukla, Westra, Shekarak Ghashghaei, and Olson (2020), which coded client motivational language, used in the present study, indicated that simulators articulated substantially higher levels of CCT, meaning that they were more resistant to change than the community volunteers. Thus, the Traditional training group behaved consistently with the findings of previous studies that higher levels of resistance evoke lower levels of Support and higher levels of Demand (Hara, Westra, Constantino, & Antony, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…As expected, the Traditional workshop trainees lowered their level of Support with simulators versus the community volunteers, but the DP group increased Support. Findings from Di Bartolomeo, Shukla, Westra, Shekarak Ghashghaei, and Olson (2020), which coded client motivational language, used in the present study, indicated that simulators articulated substantially higher levels of CCT, meaning that they were more resistant to change than the community volunteers. Thus, the Traditional training group behaved consistently with the findings of previous studies that higher levels of resistance evoke lower levels of Support and higher levels of Demand (Hara, Westra, Constantino, & Antony, 2018).…”
Section: Discussionmentioning
confidence: 65%
“…Within the field of deliberate practice of therapy skills, although a distributed approach to accessing expertise underpins the study by Chow et al. (2015), the predominant trend has been to espouse an apprenticeship model in which the learner is guided by a single authoritative coach (e.g., Anderson et al., 2019; Di Bartolomeo et al., 2020; Di Bartolomeo et al., 2020; Hill et al., 2019; Miller, Chow, et al., 2020; Miller et al., 2020; Rousmaniere, 2016; Shukla et al., 2020; Westra et al., 2020). Findings of the present study showed that students made use of multiple sources of expertise, including peers, experienced therapists (e.g., course tutors and videos of master therapists) and research evidence (e.g., measures of competence in specific skills), in a manner consistent with analyses of distributed expertise within communities of practice (Damasceno, 2018; Lave & Wenger, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Within the domain of psychotherapy, Rousmaniere (2016, 2018) has described a model of deliberate practice in which clinical supervision focused on enabling the supervisee to address skill deficits highlighted in client feedback. In studies of training workshops in specific skills, deliberate practice of modelled responses has resulted in higher level trainee skill improvement, compared with outcomes when deliberate practice was not used (Anderson et al., 2019; Di Bartolomeo et al., 2020; Di Bartolomeo et al., 2020; Hill et al., 2019; Shukla et al., 2020; Westra et al., 2020). A further pattern of deliberate practice of therapy competencies comprises self‐practice in which practitioners develop competence in therapy concepts and interventions through spending time applying these tools to issues in their own life (Bennett‐Levy, 2019; Bennett‐Levy & Finlay‐Jones, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, information technology has been widely used in the field of education. In language education, the popularity of English education in China is getting higher and higher, and the traditional language education methods are difficult to meet people's needs [1]. In this context, Computer Assisted Language Learning (CALL) has become a research hotspot [2].…”
Section: Introductionmentioning
confidence: 99%